Respuesta :
Answer:
x = 12
Step-by-step explanation:
Let's use the distributive rule first for both 5(x - 1) and 7(x + 1). When using the distributive rule to expand parentheses, remember to find the sum of the product of the "outside number" with each of the "inside numbers".
5(x - 1): 5 is the outside number and both x and -1 are the inside numbers.
5 * x + 5 * (-1) = 5x - 5
7(x + 1): 7 is the outside number and both x and 1 are the inside numbers.
7 * x + 7 * 1 = 7x + 7
Now, we can put these back into the equation:
5x - 5 + 3x = 7x + 7
Combine all the x's and the constants:
8x - 5 = 7x + 7
x = 7 + 5 = 12
Thus, the answer is x = 12.
Hope this helps!
Answer:
x = 12
Step-by-step explanation:
5(x – 1) + 3x = 7(x + 1)
5x - 5 + 3x = 7x + 7
8x - 5 = 7x + 7
8x - 7x = 7 + 5
x = 12